Effective removal of rhodamine B dyestuff using colemanite as an adsorbent: Isotherm, kinetic, thermodynamic analysis and mechanism - Feray Bayça (Heliyon)
Removal of Rhodamine B (RhB) from aqueous solutions was performed by the batch adsorption process. Colemanite was characterized as an adsorbent by Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD) and X-Ray Fluorescence (XRF). The effects of contact time, the effect of the initial concentration of the dye, the amount of adsorbent and temperature parameters on the removal of RhB were investigated. Equilibrium adsorption data of RhB on colemanite were analyzed using the Langmuir, Freundlich and Dubinin-Radushkevich isotherm models. It was found that the isotherm that showed the highest correlation with experimental data was the Langmuir isotherm. Using the Langmuir isotherm, the theoretical adsorption capacity was calculated as 42.02 mg/g. Adsorption kinetics were analyzed with Pseudo-First-Order, Pseudo-Second-Order and Intraparticle diffusion models. As a result of the calculations, it was determined that the most appropriate kinetic model was the Pseudo-Second-Order kinetic model. Thermodynamic studies have shown that adsorption is a physical, non-spontaneous, exothermic process in which randomness at the solid-liquid interface decreases. According to the results obtained, it can be said that colemanite can be used as a suitable adsorbent in the removal of Rhodamine B dye from wastewater.